FACTORS INFLUENCING CUSTOMER SATISFACTION IN ONLINE SHOPPING (International Journal of Food and Nutritional Sciences, 2022)
Purpose - The goal of this study is to examine the factors that influence customer satisfaction among internet shoppers. Customers will be satisfied as a consequence of the investigation's contribution to the design of several solutions to enhance the online purchase experience.Design/methodology/approach -Many variables affecting customer satisfaction with online purchases were examined using an online questionnaire. EFA is applied to understand the key factors that drive satisfaction among customers for online shopping. There were many statistical methods used, including information normality test, reliability analysis and regression analysis. For this research, a total of 270 internet shoppers were surveyed, with 108 men (40 percent) and 162 women (60 percent).